Perubahan Kandungan Β-Karoten, Asam Lemak Bebas dan Bilangan Peroksida Minyak Sawit Merah Selama Pemanasan - Budiyanto Budiyanto; Devi Silsia; Zulman Efendi; Rasie Janika (agriTECH, 2010)
The objectives of the study were to evaluate decreasing pattern of ß-carotene, determine the changes of free fatty acid content and to determine peroxide value of red plam olein oil during heating. Red palm olein oil samples were heated at four different temperatures (150°C, 160°C, 170°C, and 180°C) for ten hours. Heated samples were taken every 30 minutes for each heating treatment. The ß-carotene, FFA, and peroxide value in each sample were evaluated. The data were plotted into its curve for further evaluation. The finding indicated that ß-carotene content in red palm olein oil decreased sharply in the first three hours of heating, especially for the oil heated at 180°C.  In adition, heating for 10 hours resulted in decreasing of FFA and peroxide values, especially for red palm oil samples heated above 150°C.ABSTRAKPenelitian ini bertujuan untuk mengkaji pola penurunan kandungan ß-karoten, menentukan pola perubahan kandun- gan asam lemak bebas (FFA), dan menentukan pola perubahan bilangan peroksida minyak sawit merah selama pe- manasan. Minyak sawit merah dipanaskan pada empat suhu pemanasan yang berbeda  (150°C, 160°C, 170°C, dan180°C) selama 10 jam. Sampel minyak diambil setiap 30 menit dari setiap  minyak yang dipanaskan. Kandungan ß-karoten, FFA, dan bilangan peroksida pada setiap sampel dievaluasi. Data yang diperoleh dituangkan secara gra- fis untuk analisa lebih lanjut. Hasil Penelitian menunjukkan kandungan ß-karoten minyak sawit merah mengalami penurunan tajam selama tiga jam pertama pemanasan, khususnya pada minyak yang dipanaskan pada suhu 180°C. Selain itu, lama pemanasan selama 10 jam mengakibatkan terhadap turunnya kadar FFA serta penurunan bilangan peroksida,  khususnya pada minyak yang mengalami pemanasan lebih dari 150°C.